Appropriateness of Antibiotic Prescribing in Hospitalized Children: A Focus on the Real-World Scenario of the Different Paediatric Subspecialties - Nasso, Chiara; Scarfone, Alessandro; Pirrotta, Igor; Rottura, Michelangelo; Giorgi, Domenico Antonio; Pallio, Giovanni; Irrera, Natasha; Squadrito, Violetta; Squadrito, Francesco; Irrera, Pierangela; Arcoraci, Vincenzo; Altavilla, Domenica (Frontiers in Pharmacology, 2022)
Background: Antibiotics are prescribed for children both in hospital and community settings, particularly at preschool age. Italy shows a high rate of inappropriate antibiotic prescriptions which may represent a serious problem in the hospital scenario. Thus, the aim of this study was to investigate antibiotic inappropriate use in the context of different paediatric subspecialties in a hospital setting Methods: Antibiotics use was retrospectively analysed in paediatric patients (0-18 years) admitted in the emergency paediatrics, general paediatrics, paediatric nephrology and rheumatology units between January and December 2019. Patients were stratified by age in neonates, infants, toddlers, children and adolescents. Assessments were conducted by trained local assessors and appropriateness was classified as appropriate, inappropriate and not assessable. Results: Empirical antibiotics were mainly prescribed following a diagnosis of respiratory, gastrointestinal and/or urinary infection. A total of 825 antibiotic prescriptions were recorded in the three subspecialties; 462 antibiotic prescriptions (56%) out of 825 were assessed as inappropriate and 55 prescriptions (6.7%) were not assessable. Inappropriateness considerably varied within subspecialties: the risk of inappropriate antibiotic prescribing was higher in emergency paediatrics and general paediatric than… and in children, according to age. Ceftriaxone and clarithromycin were the most inappropriate prescribed antibiotics in the emergency paediatrics whereas amoxicillin/clavulanic acid represented the most inappropriate antibiotic prescribed in general paediatrics. Conclusion: The present data may be useful in order to reduce inappropriate antibiotic use in the paediatric setting; antibiotic stewardship and clinical improvement programs in hospital paediatric care are strongly recommended.